2022 International Symposium on Electromagnetic Compatibility – EMC Europe 2022
DOI: 10.1109/emceurope51680.2022.9901031
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Electromagnetic Radiation of 4G/5G Base Stations on Medical Short-Range Devices in Urban Area

Abstract: The impact of electromagnetic radiation created by micro base stations of 4G/5G cellular networks on receivers of medical short-range devices of different systems (capsule endoscopy system, body area network system, and active implant system) located inside buildings is analyzed for urban area. The analysis is made by the use of computer simulation involving the multipath radiowave propagation model which takes into account outdoor-to-indoor propagation. To perform the simulation, a 3D model of a fragment of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Their results revealed that the exposure field strength from those RF sources exceeded the minimum immunity level of 3 V/m according to IEC 60601-1-2 [2]. Another similar study was conducted by A. Svistunou et al [3] which concluded that medical short-range devices located inside hospital buildings can potentially be interfered with by 4G/5G base stations outside of the hospital buildings. As for medical devices in clinical environments, the work done by Z. Chen et al [4] showed that EMI issues such as display distortion from a medical screen monitor can be caused by the close use of an electrosurgical knife.…”
Section: Introductionmentioning
confidence: 83%
“…Their results revealed that the exposure field strength from those RF sources exceeded the minimum immunity level of 3 V/m according to IEC 60601-1-2 [2]. Another similar study was conducted by A. Svistunou et al [3] which concluded that medical short-range devices located inside hospital buildings can potentially be interfered with by 4G/5G base stations outside of the hospital buildings. As for medical devices in clinical environments, the work done by Z. Chen et al [4] showed that EMI issues such as display distortion from a medical screen monitor can be caused by the close use of an electrosurgical knife.…”
Section: Introductionmentioning
confidence: 83%